CARA MENGEMBANGKAN KECEPATAN LARI - Widodo, Slamet (Pendidikan Dan Kepelatihan Olahraga, 2010)
This writing aims to give the understanding training method to increase speed. Sprinting speed can be improved although improvement of the very limited speed, because limited by talent. Improvement of sprinting speed can be enlarged by increasing speed support components i.e ; power, anaerobic (speed endurance), flexibility, coordination and skill of run technique. Training of speed better be addressed at improvement of motion frequency by exceeding ability of motion frequency before all. Steps that need to be followed to develop speed consisted of: (1) Basic training to develop all qualities of movement to a level that will provide a solid base on which to build each successive step, (2) Weight training to develop functional strength and explosive movements against medium to heavy resistance. (3) Flexibility and ballistics training. Ballistics to develop high-speed sending and receiving movements, (4) Plyometrics to develop explosive hopping, jumping, bounding, hitting, and kicking, (5) Sprinting form and speed endurance to develop sprinting technique and improving the length of time you are able to maintain speed (6) Sport loading to develop specific speed. The intensity is 85 to 100% of maximum speed, (7) Over speed training. This involves systematic application of sporting speed that exceeds maximum speed by 5 to 10% through the use of various over speed training techniques